STUDI PERTUMBUHAN DAN PRODUKSI SISTEM TANAM DAN VARIETAS KEDELAI (Glycine max Merrill) DI ANTARA BARISAN TANAM KELAPA SAWIT UMUR 16 TAHUN - Hendra Sirait; Lisa Mawarni; Sabar Ginting (Universitas Sumatera Utara, 2013)
ABSTRACTThe objective of this research was to study growth and yield of soybean varieties on different plantspacing. This research was done in PTPN 3 Afdeling VII Kebun Rambutan, Sumatera Utara. Usingrandomized block design of two factor were plant spacing (squared and penta) and varieties ofsoybean (Anjasmoro, Nanti). The result showed that plant spacing was significantly effect to plantheight at 3 and 4 WAP (week after planting). Varieties significantly effect to plant height at 4 and 6WAP (week after planting), productivity/plot and weight of 100 seeds. The interaction of plantspacing and varieties significantly effect to leaf number.